(untitled) (Research, Society and Development, 2021)
The objective was to describe scientific evidence about the behavior and knowledge of adolescents and young people about their sexuality and ways of preventing sexually transmitted infections (STIs). Integrative review, with a qualitative approach, with the guiding question: what is the behavior and knowledge of young students about their sexuality and ways of preventing STIs?. Data collection took place in August 2020, the search was carried out in the databases of the Virtual Health Library, among them: Medline, Lilacs and BDENF, using the descriptors in Health Sciences (DeCS): Adolescent, Sexually Transmitted Infection, Knowledge and Sexual Health. 206 articles were detected, 25 of which met the inclusion criteria, after careful analysis and reading of the writings. The risk behaviors most present in the literature studies was early sexual initiation with the most vulnerable male sex, accompanied by unprotected sexual practices, without adherence in this public to the frequent use of condoms, thus increasing the risk of sexually transmitted infections. There was also a limited knowledge among adolescents about the anatomy and physiology of the external sexual organs, especially the female.